REKONSTRUKSI PENDIDIKAN AKHLAK MELALUI SINERGI TRIPUSAT PENDIDIKAN DALAM PEMBELAJARAN PAI - Hidayat, Andi; Dja'far, Abu Bakar (STKIP Pesisir Selatan, 2025)
This research is motivated by the phenomenon of Islamic religious education (PAI) in schools, which is often trapped only in the cognitive realm and the transfer of knowledge, without real application in daily behavior. Limited time allocation (2 hours of lessons per week) and evaluation orientation based solely on written tests are major obstacles in the formation of students' noble character. This study aims to analyze how the synergy between schools, families, and communities (Tripusat Pendidikan) can provide a solution to optimize the development of PAI. Using a descriptive qualitative approach, this study found that the success of PAI is highly dependent on three main pillars. First, the creativity and exemplary behavior of teachers (ing ngarso sung tulodo) as influential educators in schools. Second, the role of the family as the first madrasah (school) that carries out the habit of worship at home. Third, community support as a religious social environment. The results show that the integration of exemplary behavior, habituation, advice, and collective supervision through the Tripusat synergy can change students' paradigms that religion is a necessity of life. In conclusion, the harmonious synergy between these three educational centers can address the limited number of hours available in schools and ensure the continuous internalization of Islamic values, fostering a comprehensive character in students.